Altitude training does not improve running performance more than equivalent training near sea level in trained runners - Levine, B.; Stray-Gundersen, J. (Medicine & Science in Sports & Exercise, 1992)
Competitive distance runners (N = 19) were matched and randomized to either altitude (2,500-30,00 m) or near sea-level (1,200 m) residence and training for four weeks. Heart rate was recorded during every session, and VO2, VE, and lactate during training were measured intermittently in the field to ensure equivalent training in both groups. Laboratory tests (150 m) were also conducted as well as a 5 km time trial. Performances and physiological parameters changed similarly. Submaximal physiological responses (HR and La) were better at sea-level than altitude. Implication: Altitude training at 2,500-3,000 m provides no advantage in sea-level running performance above that obtained by equivalent supervised training near sea-level.